Groove wall type sulfur positive electrode material and preparation method thereof
By using picosecond laser processing technology to prepare the groove structure on the surface of the reduced graphene oxide aerogel of the lithium-sulfur battery positive electrode material, the problem of low utilization rate of active substances in the design of high specific energy battery is solved, and higher energy density and cycle stability are achieved.
Patent Information
- Application Number
- CN202510036566.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The sulfur positive electrode materials of existing lithium-sulfur batteries have problems such as low utilization of active substances and poor electrochemical performance in the design of high specific energy batteries. Especially under thick electrode conditions, the porosity and few charge transport paths are low, resulting in low permeability of the electrolyte and slow conversion kinetics.
The picosecond laser processing technology is used to prepare channels on the surface of reduced graphene oxide aerogel with sulfur loading to form a trench wall-shaped sulfur positive electrode material, achieving a unique layered pore wall structure, reducing tortuosity and increasing surface pore openings.
The utilization rate and electrochemical performance of the active substance of the cathode material of lithium sulfur battery are improved, the permeability of the electrolyte and the diffusion speed of lithium ions are enhanced, and the energy density and cycle stability of the battery are improved.
Smart Images

Figure CN119833612A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a groove wall type sulfur positive electrode material and a preparation method thereof. Background Art
[0002] As the main growth engine for lithium battery applications, new energy vehicles still have problems with battery efficiency and endurance. The rate of increase in the energy density of lithium-ion batteries has slowed down significantly and is gradually approaching the theoretical limit. Both from the perspective of technical realization and commercialization, it is a difficult hurdle that many car companies and battery manufacturers have to overcome. Among many electrochemical energy storage systems, lithium-sulfur batteries have unique advantages in the design of high-energy-density batteries: their positive electrode active materials are based on a multi-electron reaction mechanism, and their mass energy density is as high as 2600Wh / kg, which is about an order of magnitude higher than commercial lithium-ion batteries. The use of highly conductive porous materials as sulfur carriers can improve the electrochemical performance of lithium-sulfur batteries. Carbon materials are widely used as carrier materials for active sulfur in lithium-sulfur batteries because they have good conductivity, are low in price, and are easy to make into porous structures.
[0003] At present, lithium-sulfur batteries need to achieve high active material utilization and high volume energy density under harsh conditions of high mass loading, that is, they need to transform the current coated thin electrodes into thick electrodes. However, both the mass energy density and volume energy density of sulfur cathodes are linearly negatively correlated with their porosity. Conventional porous electrodes prepared by three-dimensional graphene (3DG) have random pore geometry and high tortuosity, and compacted electrodes have low porosity and fewer charge transfer paths, poor ion transport capacity, and low electrolyte permeability, resulting in slow sulfur conversion kinetics, low active material utilization, and thus low total battery capacity.
[0004] High energy density and ultralong cycle life are of great significance for the pursuit of practical lithium-sulfur batteries, but it is still challenging to develop sulfur cathodes with ultrathickness, ultrahigh areal capacity and stable cycling performance.
[0005] In order to improve the conductivity of sulfur, it is often necessary to introduce low-density porous carbon materials, which leads to a decrease in volume density; and in order to allow the electrolyte to fully infiltrate, it is usually necessary to construct low-tortuosity straight porous channels inside the electrode. Among them, the technology of designing oriented channel structures in thick electrodes by template method has been widely studied. However, materials prepared by ice templates or other templates require cumbersome processes and difficult-to-control straight channels, which ultimately lead to uneven channel morphology in thick sulfur positive electrodes. This inclined channel will cause different local charge states of the positive electrode, thus generating greater stress inside the sulfur particles, resulting in the shedding and fragmentation of active materials, and the loss of connection between some active materials and the conductive network, causing the battery capacity to decay. On the other hand, it is also difficult to construct rich and diverse pore structures and active sites in the voids. Summary of the invention
[0006] The object of the present invention is to provide a groove wall type sulfur positive electrode material and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] The present invention provides a method for preparing a groove wall type sulfur positive electrode material, comprising the following steps:
[0009] Picosecond laser processing is performed on the sulfur-loaded reduced graphene oxide aerogel to prepare channels on the surface, thereby obtaining the channel wall type sulfur positive electrode material.
[0010] Furthermore, the sulfur-loaded reduced graphene oxide aerogel is processed by tableting and has a thickness of 0.3-0.5 mm.
[0011] Furthermore, the pressure of the tableting process is 0.1 MPa.
[0012] Furthermore, the speed of the picosecond laser processing is 1000-2000 m / s, the power is 0.5-50 W, and the frequency is 20-40 KHz.
[0013] Furthermore, when channels are prepared on the surface of the sulfur-loaded reduced graphene oxide aerogel using picosecond laser processing, the processing spacing is 60-120 um, preferably 100 um.
[0014] Furthermore, the method for preparing the sulfur-loaded reduced graphene oxide aerogel comprises the following steps:
[0015] A reducing agent is added to a graphene oxide solution, a hydrothermal reaction is carried out at 90° C., and then the hydrothermal reaction product is freeze-dried to obtain a reduced graphene oxide aerogel;
[0016] The reduced graphene oxide aerogel is used to load sulfur to obtain the sulfur-loaded reduced graphene oxide aerogel.
[0017] Furthermore, the reducing agent is hydrazine hydrate, ascorbic acid or ethylenediamine; and the hydrothermal reaction time is 500-600 minutes.
[0018] Furthermore, in the present invention, the mass ratio of ascorbic acid to graphene oxide is 2:1, exceeding which will result in decreased conductivity of the reduced graphene oxide.
[0019] Furthermore, in the present invention, the mass ratio of sulfur to reduced graphene oxide aerogel is 7:3 to 8:2, exceeding which will result in insufficient sulfur loading or poor conductivity.
[0020] Furthermore, in the present invention, the number of picosecond laser processing times must be greater than 2 times, otherwise the surface of the channel will not be smooth; the number of processing times must be less than 8 times, otherwise the material will be burned through by the laser.
[0021] Furthermore, the linear speed of the picosecond laser can be adjusted to 1000-2000m / s during the processing, which makes the material contact with the laser for a very short time and the laser thermal effect is very small, which is particularly advantageous for the surface processing of materials with light elements such as carbon and sulfur.
[0022] In the present invention, the power (0.5-50W), frequency (20-40KHz) and processing spacing (60-120um range) during the picosecond processing also have a significant impact on the surface processing effect, and the processing parameters need to be controlled within a reasonable range.
[0023] The present invention also provides a groove wall type sulfur positive electrode material prepared by the above preparation method.
[0024] The present invention further provides application of the groove wall type sulfur positive electrode material in a sulfur-lithium battery.
[0025] Unlike most processes used for thick electrodes of lithium-sulfur batteries, the picosecond laser itself has low power and cannot melt the surface of the material, and is not suitable for metal composite materials that require laser thermal effect for surface treatment. The present invention applies laser processing technology on the surface of inorganic amorphous materials to prepare positive electrode materials for lithium-sulfur batteries. More specifically:
[0026] (1) During the synthesis of reduced graphene oxide aerogel, a porous material can be obtained through freeze-drying, which is a good preliminary design for the pore structure on the Laser-GA@S wall;
[0027] (2) During the laser processing, by rationally controlling the processing parameters, grooves with unique oriented channels can be prepared, thereby better inhibiting the dissolution of lithium polysulfide and improving the stability of the positive electrode material.
[0028] The thickness of the electrode has a direct impact on the energy density of the lithium-sulfur battery. Generally speaking, the thicker the electrode, the higher the energy density of the battery. However, since the sulfur content in the electrode material is limited, if the electrode is too thick, the sulfur in the battery will be unevenly distributed, resulting in increased internal tortuosity of the electrode, longer ion channels, and reduced utilization of active substances. This will cause the diffusion rate of lithium ions in the electrode to decrease, thereby affecting the energy density of the battery. Therefore, excessive electrode thickness will have a negative impact on the energy density of the battery. The thickness of the lithium-sulfur battery positive electrode material prepared by the coating method in general literature is in the range of 10-100um. Due to problems such as interface effects and insufficient kinetics, thick electrodes are designed through synthesis using a cumbersome template method process. Therefore, high porosity and high thickness on the positive electrode of lithium-sulfur batteries have become mutually constrained technical issues.
[0029] The present invention uses a self-assembled graphene aerogel self-supporting thick electrode as a carrier of the sulfur positive electrode, and utilizes its three-dimensional conductive network that is easy to control and has abundant micropores to achieve the loading of active sulfur. At the same time, an ultra-short pulse picosecond laser is used to process the surface of the graphene aerogel thick electrode. The ultra-short pulse picosecond laser has the characteristics of ultra-short pulse width and adjustable frequency, and belongs to a laser beam with extremely high pulse energy density. The short action time of the beam (10 -12 s level), has little thermal impact on the sulfur particles attached to the graphene surface, has the characteristics of low average energy and short action time, and can be prepared on the surface of self-supporting graphene materials to strengthen uniform channels or give the sulfur positive electrode surface porous functional properties.
[0030] The present invention firstly utilizes the gel formed by the interaction of π-π bonds of graphene oxide (GO) in a low-temperature hydrothermal environment as a three-dimensional skeleton, and freeze-dries in one step to prepare reduced graphene oxide aerogel; the present invention adopts a reducing agent to remove the oxygen-containing functional groups on the surface of graphene oxide, thereby restoring its hydrophobicity and conductivity.
[0031] Due to the presence of the hydrophobic surface of reduced graphene oxide, a hydrogel with a porous structure and a conductive network is formed during the reduction process. After freeze-drying, the morphological characteristics of the reduced graphene oxide aerogel product have an open pore structure that is easy for molten sulfur to enter, and the self-supporting sulfur-loaded thick electrode material GA@S can be obtained by directly pressing and adjusting the pressure. The present invention further adopts picosecond laser surface processing technology to design and construct a laser-processed channel on the surface of the self-supporting thick sulfur positive electrode GA@S, effectively solving the technical problems of the electrode material transmission path and ion channel being too long, the high tortuosity causing the electrolyte to be unable to penetrate, and the low utilization rate of the loaded active material. Due to the extremely small thermal energy effect of the picosecond laser and the thermal insulation characteristics of the porous structure of the graphene aerogel itself, the heat is difficult to be transferred in depth on both sides of the prepared channel, and no obvious cladding features are formed on the surface and inside of the groove, and a smooth and uniform internal surface is formed due to the extreme laser processing process.
[0032] The thick electrode processed by picosecond laser in the present invention has a unique layered pore wall structure inside, which makes the Laser-GA@S thick electrode have lower tortuosity and more surface pore openings. The porous conductive network of graphene can also be seen on the inside of the "wall". This structure can have a greater inhibitory effect on the shuttle effect of polysulfides in lithium-sulfur batteries, and the active material at the bottom of the wall can also be fully utilized as the electrolyte is immersed in the channel.
[0033] The present invention discloses the following technical effects:
[0034] The present invention uses reduced graphene oxide aerogel as a carrier of active ingredient sulfur and adopts picosecond laser processing technology to prepare a groove wall type sulfur positive electrode material. A unique layered pore wall structure can be realized inside the electrode. This structure can achieve lower tortuosity and more surface pore openings for thick electrode materials. The inside of the "wall" structure formed by the material also has a porous conductive network of graphene. This structure can have a greater inhibitory effect on the shuttle effect of polysulfides in lithium-sulfur batteries, and the active material at the bottom of the wall can also be immersed in the channel with the electrolyte to achieve full utilization.
[0035] The positive electrode material prepared by the present invention based on the picosecond laser processing technology has the characteristics of excellent performance and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 SEM images of Laser-GA@S at different resolutions in Example 1 of the present invention: a) straight grooves on the surface of Laser-GA@S; b) wall structure in the grooves of Laser-GA@S; c) pores on the wall structure of Laser-GA@S; d) locally enlarged SEM image of Laser-GA@S.
[0038] Figure 2 In the figure, a) is a microscope image of the straight grooves on the surface of the Laser-GA@S prepared in Example 1 of the present invention (the inset is a photo of the Laser-GA@S after laser processing); b) is a SEM image of the Laser-GA@S prepared in Example 1 of the present invention; c) is an EDS sulfur element scan image of the Laser-GA@S prepared in Example 1 of the present invention, and d) is an EDS carbon element scan image of the Laser-GA@S prepared in Example 1 of the present invention.
[0039] Figure 3 Performance verification of the Laser-GA@S positive electrode assembled soft-pack battery prepared in Example 1 of the present invention: a) 0.1C and 0.2C rate discharge curves and specific capacity comparison (the inset is a photo of the prepared soft-pack battery); b) the cycle capacity change curve and coulombic efficiency of the Laser-GA@S soft-pack battery (the inset is a thickness measurement photo of the Laser-GA@S positive electrode material with a thickness of 318um).
[0040] Figure 4 The microscopic morphology images of the Laser-GA@S positive electrode materials prepared in Comparative Examples 1 and 2 of the present invention; wherein a) is Comparative Example 1, and b) is Comparative Example 2.
[0041] Figure 5 The 0.1C specific capacity comparison of the Laser-GA@S positive electrode material prepared in Example 1 of the present invention and the Laser-GA@S positive electrode material prepared in Comparative Example 1 is shown. DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] The graphene oxide GO powder and ascorbic acid used in the examples of the present invention were purchased from Sinopharm Reagent Co., Ltd., and elemental sulfur was purchased from Changrui Biotechnology Co., Ltd.
[0048] Example 1
[0049] (1) Preparation of graphene oxide (GO) dispersion
[0050] GO powder was dispersed in deionized water for ultrasonic dispersion to obtain a 3 mg / mL GO dispersion.
[0051] (2) Preparation of reduced graphene oxide (rGO) aerogel blocks
[0052] a. adding ascorbic acid to the GO dispersion at a mass ratio of ascorbic acid to GO = 2:1, and further subjecting the dispersion to hydrothermal reduction at 90 °C for 500 min;
[0053] b. freeze-dry the sample obtained in step a at -50 ° C for 24 h to obtain a reduced graphene oxide (rGO) aerogel block (GA) with a thickness of 2 cm;
[0054] (3) Preparation of GA@S positive electrode self-supporting material
[0055] The sulfur element was spread onto the upper surface of the GA block and melted in a muffle furnace at 155°C to obtain a 2-cm-thick GA@S positive electrode self-supporting material (the mass ratio of elemental sulfur to GA was 7:3).
[0056] (4) Preparation of GA@S thick sulfur electrode
[0057] The prepared GA@S positive electrode self-supporting material was pressed into sheets under a pressure of 0.1 MPa to prepare a GA@S thick sulfur electrode with a thickness of 0.5 mm.
[0058] (5) Preparation of laser processed graphene aerogel (Laser-GA@S)
[0059] a. Use picosecond laser to process the surface groove, where the laser processing interval is 100um, the laser line speed is 1000m / s, and the construction of the entire straight channel is completed within 0.5ms. The number of processing times can be adjusted to 5 times according to the thickness of the GA@S thick sulfur electrode;
[0060] A picosecond fiber pulse laser of model YLPP-25-3-50-R was used, with a focused spot diameter of 40 μm. The laser processing parameters were as follows: wavelength 1030 nm; laser power 20 W; frequency 20 khz; pulse width less than 15 ps.
[0061] Assemble 2032 button cell battery:
[0062] The prepared Laser-GA@S slices were cut into lithium sheets as negative electrodes, Celgard separators were used, and the electrolyte concentration was 1 mol L -1 1,3-dioxolane (DOL)-ethylene glycol dimethyl ether (DME)-based bistrifluoromethanesulfonyl imide lithium (LiTFSI) electrolyte, recorded as LiTFSI / DOL-DME (volume ratio 1:1), and 0.1 mol L -1 LiNO3 is assembled into button batteries.
[0063] The battery performance was tested, in which the sulfur content in the positive electrode was 60%.
[0064] Figure 1 SEM images of Laser-GA@S at different resolutions: a) straight grooves on the surface of Laser-GA@S; b) wall structure inside the grooves of Laser-GA@S; c) pores on the wall structure of Laser-GA@S; d) locally enlarged SEM image of Laser-GA@S.
[0065] Figure 2 In the figure, a) is a microscope image of the straight grooves on the surface of Laser-GA@S (the inset is a photo of Laser-GA@S after laser processing); b) is a SEM image of Laser-GA@S; c) is an EDS sulfur element scan image of Laser-GA@S, and d) is an EDS carbon element scan image of Laser-GA@S.
[0066] Figure 3 The performance verification of the Laser-GA@S positive electrode assembled soft-pack battery prepared in Example 1 of the present invention: a) 0.1C and 0.2C rate discharge curves and specific capacity comparison (the inset is a photo of the prepared soft-pack battery); b) the cycle capacity change curve and coulomb efficiency of the Laser-GA@S soft-pack battery (the inset is a photo of the thickness measurement of the Laser-GA@S positive electrode material with a thickness of 318um). It can be seen that the prepared Laser-GA@S positive electrode material has a high sulfur loading (7mg / cm 2 ), thickness greater than 300um, and achieved high active material utilization and high area capacity, as well as stable cycle stability, with improved specific capacity and cycle performance. At a rate of 0.1C, the discharge capacity of the first cycle reached 1090mAh / g, and the coulombic efficiency of the first 100 cycles remained at 88.2%; at a rate of 0.2C, the first cycle discharge capacity was still 945mAh / g, which has potential commercial value.
[0067] Comparative Example 1
[0068] The only difference from Example 1 is that the laser speed is adjusted from 1000 m / s to 500 m / s; and the power is adjusted from 20 W to 15 W.
[0069] Figure 4 In the figure, a) and b) are the microscopic morphology images of the Laser-GA@S positive electrode material prepared in Comparative Example 1 at different magnifications; wherein, a) is the SEM image of the groove processed at a scan rate of 500 m / s and a power of 15 W, and it can be seen that the grooves obtained by setting the scanning line speed and power of the ultrafast pulse laser differently have residual burrs and burrs, and b) is the non-smooth burr structure at a magnification.
[0070] Figure 5 The 0.1C specific capacity comparison of the Laser-GA@S cathode material prepared in Example 1 and the Laser-GA@S cathode material prepared in Comparative Example 1 is shown in FIG. Figure 5 It can be seen that inappropriate coordination of laser speed and power during processing will result in the inability to form a smooth wall structure, which in turn affects the utilization rate of the active substance sulfur and reduces the specific capacity of the lithium-sulfur battery.
[0071] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a groove wall type sulfur positive electrode material, characterized in that: The following steps are involved: Picosecond laser processing is performed on the sulfur-loaded reduced graphene oxide aerogel to prepare channels on the surface, thereby obtaining the groove wall type sulfur positive electrode material.
2. The preparation method according to claim 1, characterized in that: The sulfur-loaded reduced graphene oxide aerogel is processed by tabletting and has a thickness of 0.3-0.5 mm.
3. The preparation method according to claim 2, characterized in that: The pressure of the tableting process is 0.1 MPa.
4. The preparation method according to claim 1, characterized in that: The speed of the picosecond laser processing is 1000-2000 m / s, the power is 0.5-50 W, and the frequency is 20-40 KHz.
5. The preparation method according to claim 1, characterized in that: When channels are prepared on the surface of sulfur-loaded reduced graphene oxide aerogel using picosecond laser processing, the processing spacing is 60-120um.
6. The preparation method according to claim 1, characterized in that: The method for preparing the sulfur-loaded reduced graphene oxide aerogel comprises the following steps: A reducing agent is added to a graphene oxide solution, a hydrothermal reaction is carried out at 90° C., and then the hydrothermal reaction product is freeze-dried to obtain a reduced graphene oxide aerogel; The reduced graphene oxide aerogel is used to load sulfur to obtain the sulfur-loaded reduced graphene oxide aerogel.
7. The preparation method according to claim 6, characterized in that: The reducing agent is hydrazine hydrate, ascorbic acid or ethylenediamine; and the hydrothermal reaction time is 500-600 minutes.
8. The preparation method according to claim 6, characterized in that: The mass ratio of the sulfur to the reduced graphene oxide aerogel is 7:3 to 8:
2.
9. A groove wall type sulfur positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the groove wall type sulfur positive electrode material according to claim 9 in a sulfur-lithium battery.
Citation Information
Patent Citations
Lithium sulphur battery anode material and preparation method thereof
CN108232135A
Positive electrode for lithium-sulfur secondary battery having pattern, manufacturing method therefor, and lithium-sulfur secondary battery including same
CN113812017A
Modification method of graphite negative plate of lithium ion battery
CN114005963A
Assembly process of battery pole piece on circuit board
CN117199545A
Method for improving fast charging performance of lithium battery, negative electrode and battery
CN118782739A
Cited By
Preparation method and application of biomass thick electrode
CN120048860A